Pengaruh Kegiatan Samping Jalan Terhadap Kecelakaan Lalu Lintas (Studi Kasus Ruas Jalan By Pass Soekarno-Hatta Bandar Lampung) - Jaya, Bagus Danang; Putra, Sasana; Diana, I Wayan; Karami, Muhammad (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2021)
Traffic accidents are serious problem in Bandar Lampung City, especially the Soekarno-Hatta Bandar Lampung By Pass Road, considering that this road is the primary arterial road that should not be disturbed by shuttle traffic, local traffic, and local activities. Roadside activities are one of the disruptions that can cause accidents and need to be analyzed. Blackspot are determined by the Equivalent Accident Number (EAN) method based on accident fatality rate each segment of the road. Roadside activities are grouped into pedestrians and crossers (PED), park and stop vehicles on the side of the road (PSV), slow moving vehicles (SMV), also enter and exit vehicles of activity centers (EEV). Analysis with linear regression is used to calculate the level of impact of roadside activities with accident rates. From 25 segments along Soekarno-Hatta Road, 16 segments are classified as blackspot and 6 segments are still classified as blackspot until 2017. EEV is the highest number that affects the decrease in the number of accidents, PSV for the 2nd number, SV for the 3rd number and PED for the smallest number. Besides the average vehicle speed is only 42,8 km/h due to the high volume of vehicles with an average of 2708 skr/h also the damaged of some segments and poor support facilities of the road.